1999
DOI: 10.1002/(sici)1097-0215(19990909)82:6<822::aid-ijc9>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic genetic alterations (loh) in benign, borderline and invasive ovarian tumours: Intratumoral molecular heterogeneity

Abstract: Loss of heterozygosity (LOH) affects a number of chromosome regions in ovarian cancer, pointing to the possible involvement of tumour-suppressor genes in ovarian tumorigenesis. We performed comparative analysis of allelic loss at 6 frequently affected chromosome regions in a panel of 53 benign, borderline and malignant ovarian tumours. Precursor lesions could provide evidence that an accumulation of genetic events is required for normal ovarian epithelium to generate malignant tumours. LOH on chromosome 1p was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Some studies of benign ovarian tumors have reported low or zero rates of loss leading to speculation that these represent a distinct biological entity from malignant ovarian tumors 11, 26, 27. However, such conclusions have been based on very small numbers of tumors.…”
Section: Discussionmentioning
confidence: 47%
“…Some studies of benign ovarian tumors have reported low or zero rates of loss leading to speculation that these represent a distinct biological entity from malignant ovarian tumors 11, 26, 27. However, such conclusions have been based on very small numbers of tumors.…”
Section: Discussionmentioning
confidence: 47%
“…DCC gene belongs to a family of dependence receptors and locates on chromosomal region 18q21, which is one of the most commonly deleted regions in epithelial ovarian cancer detected by loss of heterozygosity 24 and comparative genomic hybridization analyses. 25 In the present study, the existence of a common precursor cell of stroma and epithelium is supported by the notion that loss of the DCC locus, the most frequently observed alteration in this study, was detected either in both epithelial and stromal compartments of the tumor or in none of them.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In an allelotype study of ovarian tumors, which included use of one marker at 18q, there was frequent allelic loss at D18S50 (18q23) in high-grade and -stage ovarian carcinomas, but not in well-differentiated carcinomas, borderline or benign tumors. 31 Interestingly, in a recent genome-wide analysis of copy number changes in ovarian carcinoma, an association between loss of 18q and reduced survival duration was found. 32 However, multivariate analysis of our data showed only tumor grade to be an independent prognostic factor, not tumor stage or LOH status.…”
Section: Discussionmentioning
confidence: 99%